TUBERCULOSIS PREVENTION BEHAVIOR AND RELATED FACTORS (STUDY AT NAIBONAT PRIMARY HEALTH CENTER, KUPANG REGENCY, 2023): Perilaku Pencegahan Tuberkulosis Dan Faktor-Faktor Yang Berkaitan (Studi Di Puskesmas Naibonat Kabupaten Kupang Tahun 2023) - Retnowati Nes, Ester; Krisno Syamruth, Yendris; Bestalonia Sir, Amelya (Jurnal Berkala Epidemiologi, 2024)
Background: Tuberculosis (TB) Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which attacks the lungs and other organs. Purpose: To determine the relationship between the level of knowledge, attitudes, and preventive actions of Tuberculosis disease and TB incidence in the Naibonat Health Center working area 2023. Methods: The research design used was case-control by conducting analytical observations. Using a simple random sampling technique, the sample consisted of 41 cases and 41 controls. Data analysis used the chi-square test at a significance level of 95%. (α = 0.05). Results: Based on the research shows that there is a significant relationship between knowledge (p=0.00; OR=5.98), attitude (p=0.00; OR=4.66), TB prevention actions (p=0.01; OR=5.20) on the incidence of TB at the Naibonat Primary Health Center.  Conclusion: The knowledge, attitudes, and preventive measures are significantly related to the incidence of pulmonary TB in the Naibonat Health Center working area. The community is expected to be able to pay attention to the environment where they live, have clean living behavior, and be able to participate in educational activities/socialization (counseling) related to Pulmonary TB conducted by health centers, NGOs, or health workers which help increase public knowledge.